Development of a RADEC-Based E-LKPD Using Liveworkaheets for Thermochemistry Learning - Putri, Nadila; Erviyenni, Erviyenni; Wulandari, Putri Adita (Universitas Pendidikan Mandalika, 2025)
This study aims to develop an Electronic Student Worksheet (E-LKPD) based on the RADEC (Read, Answer, Discuss, Explain, Create) learning model using the Liveworksheets platform to enhance learning quality and student engagement. The study employed the 4-D development model (Define, Design, Develop, Disseminate), limited to the development stage. The research instruments consisted of expert validation sheets and user response questionnaires. Data were analyzed using descriptive quantitative and qualitative techniques. Quantitative data were obtained from expert validation questionnaires and teacher and student response questionnaires, while qualitative data were derived from observations and open-ended responses, analyzed through data reduction, data display, and conclusion drawing. The validation results from two material experts indicated that the E-LKPD achieved validation scores ranging from 91.6% to 95.8%, categorized as “Valid.” Meanwhile, media validation by one media expert resulted in a score of 100%, also categorized as “Valid.” Trials involving teachers yielded a response score of 90.63%, and trials involving students obtained 92.32%, both classified as “Very Good.” Therefore, the RADEC-based E-LKPD was declared valid and received highly positive responses, indicating its potential for use in teaching thermochemistry to Grade XI SMA/MA students.